W kwestii zainteresowania wiedzą o pomyślnym kreowaniu nowoczesnej osobowości - Radziewicz- Winnicki, Andrzej (Pedagogika Społeczna Nova, 2023)
The aim of this scientific research is to rethink the relationship between educational and political philosophy and expected socialization practice. The article is an appeal about metaphilosophical considerations in fields of philosophy, sociology, pedagogy and also psychology. Those analyses in fields of theoretical research should allow to define the status of presented socio pedagogical reflection as well as their limitations, which are related to the attempts to provide an expansive definition of modern social pedagogy. Based on a comparison sociology of education and social pedagogy merge many of them.